(untitled) (مجلة البحوث الأكاديمية, 2025)
Background: Developmental dysplasia of the hip (DDH) includes a spectrum from mild dysplasia to complete dislocation. Early treatment improves outcomes and reduces complications. Objective: To assess clinical and radiological outcomes of closed reduction and static long leg spica casting in children aged 6–18 months with DDH. Methods: This retrospective study included 29 patients (38 hips) treated at Misurata Medical Center in 2018. All underwent adductor tenotomy, closed reduction, and hip spica casting. Outcomes were assessed using McKay’s criteria and Severin classification. AVN was evaluated by Salter’s criteria. Results: 70% of hips had good radiological outcomes; 89% showed good clinical outcomes. AVN occurred in 7.89% of cases. Mean casting duration was 90 days. Conclusion: Closed reduction and spica casting is effective and safe for managing DDH in children 6–18 months, with high success rates and low complication risk when properly applied.